Shah ʻAbbas: the king who refashioned Iran - Quinn, Sholeh Alysia (A Oneworld book, 2015)
"In this wide-ranging profile, Sholen A. Quinn explores Shah ʻAbbas's rise to power and his subsequent interactions with religious movements and artistic developments, reaching beyond the historical narrative to assess the true impact of the man and his politics."--Page 4 of cover